Correction to: Psychosocial interventions for pain management in advanced cancer patients: a systematic review and meta-analysis - Warth, Marco; Zöller, Joshua; Köhler, Friederike; Aguilar-Raab, Corina; Keßler, Jens; Ditzen, Beate (Current oncology reports, 2021)
A Correction to this paper has been published: https://doi.org/10.1007/s11912-021-01063-5